The shadow of the death penalty in Israel: constructing enemies, citizens, and victims - Ben-Natan, Amadar (The Elgar companion to capital punishment and society, 2024)
Israeli discourse over the death penalty is highly political, connecting the Holocaust and the Israeli-Palestinian conflict. Israel abolished the death penalty for criminal murder but retained it for political offenses reflecting “enemy penology”: treason, terrorism, and genocide. In practice, Israel executed only the Nazi criminal Adolf Eichmann, refraining from executions even for the bloodiest terrorist attacks. Military courts, used to prosecute Palestinians, handed down death sentences that have all been revoked, resulting in de facto abolition. By historically analyzing the law, practice, and judicial discourse in military and civilian capital cases, this chapter makes three arguments. First, enemies are constructed on a scale of multiple categories, such as Nazis, traitors, and terrorists. Second, de facto abolition maintains the shadow of the death penalty over enemy populations. This shadow laid heavier on Palestinian citizens of Israel, constructed as “citizen-enemies,” carrying the double brunt of terrorism and treason. The courts created an inverted hierarchy that enhanced punishments of citizens. Third, enemy penology functions on a symbolic level that contrasts evil enemies with an ahistoric self-image of victimhood.